Stingless bees: uses and management by meliponiculturist women in the Chaco region of Bolivia - Marcia Adler; Luciana Escóbar-Márquez; Maria Teresa Solis-Soto; Carlos F. Pinto (BMC, 2023)
Abstract Background Stingless bees have a great value as main pollinators of wild flowering and cultivated plants, thus playing a fundamental role in the maintenance of biodiversity and food security in Latin America. Despite their importance, stingless bees face numerous threats causing alarming population declines. Moreover, stingless bees have a great cultural and traditional value, since most products from the hive are used for a wide variety of purposes. A growing number of initiatives are encouraging the breeding of these bees, through training courses and modern management techniques. This study documents the knowledge on stingless bees and their products that meliponiculturists from the Chaco region of Bolivia have, as well as the influence that meliponiculture initiatives have on the management and general knowledge of the bees. Methods Local richness and diversity of stingless bees was calculated using Hill numbers. Structured interviews were conducted with 59 meliponiculturists in order to characterize traditional and formal knowledge on stingless bees and meliponiculture. Generalized linear models were applied to assess the influence of training courses on the management of the bees. Also, a relative cultural importance index was calculated for each species. Results Twelve Meliponini species were identified, and 15 local names were reported with morphological, defensiveness behavior, and nest description. There was no significant difference in the knowledge between different ethnical backgrounds or ages. A significant difference was observed in the use of supplementary feeding and assisted division, but none in the success in racking hives or in pest management, regarding the number or courses taken. The relative cultural importance index recorded 30 specific uses for bee products grouped in four categories, from which 29 were attributed (but not exclusively) to Tetragonisca angustula, making it the most versatile species. Conclusions The products of the hive, especially honey, are used for a wide variety of purposes, mostly in medicine. These uses are mostly attributed to just one species, T. angustula, in coincidence with what was taught in meliponiculture training courses by NGOs. The influence of formal knowledge is mostly positive, but it is recommended that other meliponini species are taken into account as well.